Marina Mahathir [Malaysia, Activist] - Mahathir, Marina (Institutional Knowledge at Singapore Management University, 2016)
Daughter of Malaysian Prime Minister and socio-political activist Marina Mahathir, shares with DNA on her schooling days, her views on censorship, education system, leadership crisis, and religious movements. Her work in helping HIV-infected women has led her to seek larger democratic space for everyone.